The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000430766
|View full text |Cite
|
Sign up to set email alerts
|

Mild to Moderate, but Not Minimal or Severe, Acute Histologic Chorioamnionitis or Intra-Amniotic Inflammation Is Associated with a Decrease in Respiratory Distress Syndrome of Preterm Newborns without Fetal Growth Restriction

Abstract: Background: Acute histologic chorioamnionitis (acute-HCA) is known to be associated with a decreased risk of respiratory distress syndrome (RDS) in newborns. However, there is no information about whether the severity of acute-HCA or intra-amniotic inflammation (IAI) is associated with the development of RDS. Objectives: To assess the relationship between the severity of acute-HCA or IAI and the development of RDS in preterm newborns due to preterm labor and intact membranes (PTL) or preterm premature rupture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…RDS were similar among the groups. Current evidence has shown the higher risk of RDS in infants with placental abruption, and it is already known that CA decreases the risk of RDS (36,37). In contrast, we did not find any relationship between CA and risk of RDS (26,38).…”
Section: Discussioncontrasting
confidence: 93%
“…RDS were similar among the groups. Current evidence has shown the higher risk of RDS in infants with placental abruption, and it is already known that CA decreases the risk of RDS (36,37). In contrast, we did not find any relationship between CA and risk of RDS (26,38).…”
Section: Discussioncontrasting
confidence: 93%
“…Intra-amniotic inflammation was defined as an elevated amniotic fluid matrix metalloproteinase-8 (MMP-8) concentration (>23 ng/mL), as previously reported 15, 146155 . Other studies showed that amniotic fluid MMP-8 concentration is a sensitive and specific index of intra-amniotic inflammation 151, 156–166 and correlates with an amniotic fluid white blood cell count 156, 158, 159 .…”
Section: Methodsmentioning
confidence: 99%
“…RDS was diagnozed in the presence of an increase in oxygen requirement (FiO 2 >0.4), respiratory distress symptoms, radiological findings (i.e., reticulogranular pattern and/or air bronchogram), and laboratory findings (i.e., PaO 2 less than 50 mmHg with room air, or a necessity for additional oxygen to maintain a PaO 2 greater than 50 mmHg, if arterial sampling performed) when other causes of respiratory distress was absent according to previously published criteria …”
Section: Methodsmentioning
confidence: 99%
“…An ideal preterm reference group for the comparison with preterm FGR group should include cases without FGR in the setting of acute inflammation‐free placenta. Moreover, the selection of an adequate preterm reference group is essential for the RDS research in preterm gestations because fetal lung maturation may be accelerated in preterm neonates born to mothers with intra‐uterine infection or inflammation although some human studies do not demonstrate this relationship between acute‐HCA and RDS …”
Section: Introductionmentioning
confidence: 99%